Stigmatization as a social process - Jugović Aleksandar (Temida)
The paper deals with the analysis of stigmatization as a social process. The main purpose is to explain multidimensional aspects of stigmatization. This paper reviews the key theoretical roots of ideas about stigmatization as a social process and explores a notion of social deviance, as well as the social construction and production of the deviance. The analyses indicate the main dimensions of stigmatization as a social process. These are following dimensions: time, spatial or socio-cultural, socio-stratification, gender-consequential, ideological-political, reactive and socio-psychological dimension. .